Nasal Polyposis Pathogenesis, Medical and Surgical Treatment - Önerci, T. Metin; Ferguson, Berrylin J. (Springer Berlin Heidelberg : Imprint: Springer, 2010)
Nasal rhinitis polyposis not only decreases the quality of life of affected patients, but the relationship between the upper and lower respiratory tract makes the treatment of this condition of critical importance. New research findings, as well as new technical developments, have changed the conventional medical and surgical approaches to the treatment of nasal polyposis, which has resulted in significant advances in the management of the disease. This reader-friendly and lavishly illustrated book is written by authors internationally recognized for their laboratory research and clinical practice in this field. It includes the latest information, and aims to help the reader improve the daily management of patients affected by nasal polyposis.